"Don't Be Afraid": Exploring Methodological Relationships in (Re)searching the Experiences of Immigrant Teachers of Color. (2nd January 2021) - McDevitt, Seung Eun
Abstract : In this personal essay, I revisit the research I conducted as a novice researcher on the experiences of immigrant teachers and examine the development of my reflexive-self as a researcher and an immigrant in and through my methodological relationships with the teachers. Coupled with my researcher journal, the interview conversations in which I inserted myself, the researcher, in dialogue with my participants, are analyzed through a reflexive lens to reveal how meaning was co-constructed. Making myself, including my biography and identities, visible in the research process stirred our methodological relationships to produce original narratives from the immigrant teachers of color and, ultimately, authenticated the research process as a whole. I also discuss the benefits I reaped from becoming a reflexive and vulnerable researcher, having turned my research lens back on myself, and taking responsibility for the kinds of knowledge produced in and through the study.